2021
DOI: 10.1002/jper.21-0288
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the decision to rehabilitate the posterior maxilla following surgical closure of oroantral communications/fistulae – A cohort study

Abstract: Background: Search of the English literature yielded no studies assessing the chosen dental treatment following surgical closure of oroantral communication/oroantral fistula (OAC/OAF). The purpose of the present study was to assess factors affecting the decision to rehabilitate the posterior maxilla following surgical closure of OAC/OAF. Methods: Consecutive patients at a single center. A structured form served to collect the data. The differences between groups (cases with versus cases without restoration) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…In every OAF case, maintaining a disease-free maxillary sinus membrane without infective microorganism is important for the functional recovery of maxillary sinus. In line with our study, previous study16 suggested 6 to 12 months waiting period after OAF closure for implant rehabilitation 16. A regular follow-up through clinical and radiographic examinations after the MESS with at least 4 to 5 symptoms among 7 sinonasal symptoms including nasal obstruction with facial pain, purulent rhinorrhea, foul odor, foul taste, headaches, anterior maxillary tenderness, and postnasal drip should be resolved 1.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In every OAF case, maintaining a disease-free maxillary sinus membrane without infective microorganism is important for the functional recovery of maxillary sinus. In line with our study, previous study16 suggested 6 to 12 months waiting period after OAF closure for implant rehabilitation 16. A regular follow-up through clinical and radiographic examinations after the MESS with at least 4 to 5 symptoms among 7 sinonasal symptoms including nasal obstruction with facial pain, purulent rhinorrhea, foul odor, foul taste, headaches, anterior maxillary tenderness, and postnasal drip should be resolved 1.…”
Section: Discussionsupporting
confidence: 78%
“…In line with our study, previous study 16 suggested 6 to 12 months waiting period after OAF closure for implant rehabilitation. 16 A regular follow-up through clinical and radiographic examinations after the MESS with at least 4 to 5 symptoms among 7 sinonasal symptoms including nasal obstruction with facial pain, purulent rhinorrhea, foul odor, foul taste, headaches, anterior maxillary tenderness, and postnasal drip should be resolved. 1 Moreover, water's view plays important role in determining the changes of air-fluid level of maxillary sinus in every periodic follow-up.…”
Section: Discussionmentioning
confidence: 99%